2016
DOI: 10.1021/acscatal.6b01101
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenized Iridium Water-Oxidation Catalyst from a Silatrane Precursor

Abstract: A pentamethylcyclopentadienyl (Cp*) iridium water-oxidation precatalyst was modified to include a silatrane functional group for covalent attachment to metal oxide semiconductor surfaces. The heterogenized catalyst was found to perform electrochemically driven water oxidation at an overpotential of 462 mV with a turnover number of 304 and turnover frequency of 0.035 s–1 in a 0.1 M KNO3 electrolyte at pH 5.8. Computational modeling of the experimental IR spectra suggests that the catalyst retains its Cp* group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(121 citation statements)
references
References 40 publications
6
115
0
Order By: Relevance
“…The dimeric nature of this type of iridium catalysts is also supported by kinetic analysis of the reaction progress . When mononuclear iridium catalyst 4 was anchored to an ITO surface, with no freedom to come in close proximity to a second iridium center, preventing ROC, indeed a much higher overpotential of 462 mV was found at the onset of water oxidation (Figure , 4@MO x ) …”
Section: Experimental Examplesmentioning
confidence: 79%
“…The dimeric nature of this type of iridium catalysts is also supported by kinetic analysis of the reaction progress . When mononuclear iridium catalyst 4 was anchored to an ITO surface, with no freedom to come in close proximity to a second iridium center, preventing ROC, indeed a much higher overpotential of 462 mV was found at the onset of water oxidation (Figure , 4@MO x ) …”
Section: Experimental Examplesmentioning
confidence: 79%
“…With reactions selective for the tris-pyalk species, yields of mono- and bis-chelate species were low to trace. Complex 8 was prepared in this manner, as reported previously, 27 in poor yield (8%, Scheme 3). The same reported reaction also produced very small amounts of 3–7 (below 1% for most), which was unfeasible for bulk preparation.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Brudvig and Wang showed that the same molecular Ir WOC can be successfully heterogenized onto hematite . The functionalization in the periphery of 4 with a silatrane functional group allowed for a covalent attachment to metal oxide semiconductor surface (ITO and TiO 2 ) and the assembly of photoanodes from a SnO 2 film, sensitized with a combination of a high‐potential CF 3 ‐substituted porphyrin dye …”
Section: Heterogenized Ir Wocsmentioning
confidence: 99%
“…The strategies to minimize the contents of iridium foresee the exploitation of molecular Ir WOCs (Figure A), under the assumption that all Ir‐centers are catalytically active, differently from what happens in heterogeneous IrO 2 . Otherwise, it is conceivable to anchor a well‐defined molecular Ir WOC onto a suitable support, thus obtaining a heterogenized WOC (Figure B), combining the positive aspects of homogeneous and heterogeneous catalysis. Finally, the minimization of Ir‐atoms can be achieved by diluting them in a proper material (Figure C), having features that maximize Ir‐accessibility and performance .…”
Section: Introductionmentioning
confidence: 99%